2021
DOI: 10.2147/cmar.s288007
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Nasopharyngeal Papillary Adenocarcinoma: A Review of 28 Patients in a Single Institution

Abstract: Low-grade nasopharyngeal papillary adenocarcinoma (LGNPPA) is a rare nasopharyngeal tumor. This study aimed to analyze the clinical and histopathological features of the disease, and to share our experience of its treatment. Patients and Methods: We collected demographic data, clinical symptoms, tumor location, pathological features, immunohistochemical results, treatments, and outcomes of 28 patients with pathologically confirmed LGNPPA between 2009 and 2019. Results: The median age of the 28 patients was 41.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 18 publications
4
41
0
Order By: Relevance
“…NPAC may appear in any part of the nasopharynx, but it most commonly involves the roof, the lateral, and the posterior wall [ 4 ]. It presents as a soft, slow-growing exophytic mass with a papillary or polypoid appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPAC may appear in any part of the nasopharynx, but it most commonly involves the roof, the lateral, and the posterior wall [ 4 ]. It presents as a soft, slow-growing exophytic mass with a papillary or polypoid appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal obstruction is the most common manifestation [ 1 , 3 ]. Only a limited number of cases of NPACs has been reported in the literature because these neoplasms are extremely rare [ 4 , 5 ]. As clinical presentation could be easily underestimated, an index of suspicion is necessary for a timely diagnostic and therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Complete surgical excision has been considered the treatment of choice for most cases of NPAC. [ 1 4 6 8 9 10 11 ] In their study, Takakura et al [ 10 ] found out that among the 28 case reports of NPAC they reviewed, all cases were treated with complete resection and without adjuvant treatment. Endoscopic surgery was performed in 16 cases (57.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Though controversy exists regarding the optimal treatment due to the rarity of this tumour,[ 8 ] complete surgical excision, with or without the aid of endoscope, has been considered the treatment of choice for most cases of NPAC. [ 1 4 6 8 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Lowgrade nasopharyngeal papillary adenocarcinoma (LGNPPA) is extremely rare among nasopharyngeal neoplasms. To our knowledge, fewer than 70 cases have been publicly reported thus far (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Because of the very low incidence of this disease, there are no guidelines or protocols developed for proper, standardized therapy.…”
Section: Introductionmentioning
confidence: 99%